Cancer patients' information needs and information seeking behaviour: in depth interview study. Issue 7239 (1st April 2000) - Leydon, Geraldine M; Boulton, Mary; Moynihan, Clare; Jones, Alison; Mossman, Jean; Boudioni, Markella; McPherson, Klim
Abstract: Objectives: To explore why cancer patients do not want or seek information about their condition beyond that volunteered by their physicians at times during their illness. Design: Qualitative study based on in-depth interviews. Setting: Outpatient oncology clinics at a London cancer centre. Participants: 17 patients with cancer diagnosed in previous 6 months. Main outcome measures: Analysis of patients' narratives to identify key themes and categories. Results: While all patients wanted basic information on diagnosis and treatment, not all wanted further information at all stages of their illness. Three overarching attitudes to their management of cancer limited patients' deon with life as normal and could be maintained through silence and avoiding information, especially too detailed or "unsafe" information. Charity to fellow patients, especially those seen as more needy than themselves, was expressed in the recognition that scarce resources—including information and explanations—had to be shared and meant that limited information was accepted as inevitable. Conclusions: Cancer patients' attitudes to cancer and their strategies for coping with their illness can constrain their wish for information and their efforts to obtain it. In developing recommendations, the government's cancer information strategy should attend to variations in patients' desires for information and the reasons for them.